Selecting and Preparing Poultry for Exhibition - Beyer, R. S.; Gadberry, Milton (My University, 1999)
Growing, selecting and preparing exhibition poultry for show is a good way to learn animal husbandry. The project provides an opportunity to learn responsibility, decision making and showmanship skills.
L771_1999-04
Keywords: L771; Livestock; L